ARAHAN KONSERVASI DAS DENGAN MODELAGNPS :STUDI KASUS PADA DAS BILA BULU CENDRANAE - Lukman, Melly (JURNAL SUMBER DAYA AIR, 2018)
Soil and water conservation activities in a watershed must be monitored, so that results in watershed management are known. The activities are to be implemented using an accurate method for evaluating the impact of conservation activities in accordance with the improvement of watershed condition. Evaluation of watershed condition should use hydrology parameters measured at the outlet of a watershed, and be explained quantitatively as a result of direct measurement. Such kind of evaluation can be used if appropriate instruments have been placed in the watershed. The number of watersheds or sub-watersheds provided with sufficient amount of instruments is very limited. Using a model to evaluate the watershed condition is one of the alternatives in finding solution to the above-mentioned problem. One of these models is the AGNPS Model. A study with application of such model was carried out in the Bila Bulu CendranaE watershed (South Sulawesi), and results show that the second scenario is the most suitable to improve the Bila Bulu CendranaE watershed condition.